Cytogenetic comparison of the white Cachama progeny karyotype (Piaractus orinoquensis) obtained with fresh and cryopreserved semen (Revista Sistemas de Producción Agroecológicos, 2026)
Cytogenetics facilitates the analysis of chromosomal integrity to identify potential alterations derived from the use of reproductive biotechnologies, such as cryopreserved semen in the production of native fish of economic importance as Piaractus orinoquensis, a species distinguished from its relatives through genetic and morphological methods. The demand for techniques that facilitate artificial reproduction in non-seasonal periods drove the development of semen cryopreservation, a technique that expands gamete accessibility throughout the year and helps mitigate the restrictions of reproductive management linked to seasonal cycles in this species native to the Colombian Orinoquia. The objective was to compare the karyotypes of progenies of cachama blanca (Piaractus orinoquensis) fertilized with fresh versus cryopreserved semen, evaluating differences in genetic and chromosomal quality between both reproductive strategies. This study applied the protocol of Bertollo et al. (1978), with methods of collection, fixation, and chromosomal examination in renal cells. Chromosomes from offspring generated with fresh and cryopreserved semen were analyzed, revealing 27 chromosomal pairs without significant morphological changes between groups.
Keywords: Biotechnologies; Karyotypes; Cytogenetics; Chromosomes